LA PHRASEOLOGIE EST L’ETUDE DES EXPRESSIONS LEXICALE - Qo‘ziyeva , M.Sh.; Axmedov , X.A. (Educational Research in Universal Sciences, 2023)
In this article, we have currently considered the most controversial issue of defenetion in terms of phraseology that are used in the field certain types of terms as well as the combination of words along the path devoted to the problem.